Prognostic significance of serum cytokines during acute exacerbation of idiopathic interstitial pneumonias treated with thrombomodulin. Issue 1 (29th July 2021) - Arai, Toru; Matsuoka, Hiroto; Hirose, Masaki; Kida, Hiroshi; Yamamoto, Suguru; Ogata, Yoshitaka; Mori, Masahide; Hatsuda, Kazuyoshi; Sugimoto, Chikatoshi; Tachibana, Kazunobu; Akira, Masanori; Inoue, Yoshikazu
Abstract : Background: Acute exacerbation (AE) has been reported to herald a poor prognosis in idiopathic pulmonary fibrosis and is now thought to do so in idiopathic interstitial pneumonias (IIPs). However, the pathophysiology of AE-IIPs is not sufficiently understood. In our previously reported SETUP trial, we found better survival in patients with AE-IIPs treated with corticosteroids and thrombomodulin than in those treated with corticosteroids alone. In that study, we collected serum samples to evaluate changes in cytokine levels and retrospectively examined the prognostic significance and pathophysiological role of serum cytokines in patients with AE-IIPs. Methods: This study included 28 patients from the SETUP trial for whom serial serum samples had been prospectively obtained. AE-IIPs were diagnosed using the Japanese Respiratory Society criteria. All patients were treated with intravenous thrombomodulin and corticosteroids from 2014 to 2016. Serum levels of 27 cytokines were measured using Bio-Plex. The high-resolution CT pattern at the time of diagnosis of AE was classified as diffuse or non-diffuse. Results: Univariate analysis revealed that higher serum levels of interleukin (IL)-2, IL-7, IL-9, IL-12, IL13, basic fibroblast growth factor, granulocyte-macrophage colony-stimulating factor, interferon-γ inducible protein-10, platelet-derived growth factor and regulated on activation, normal T cell expressed and secreted (RANTES) at AE were significant predictors of 90-day survival. The HRCT pattern was also a significant clinical predictor of 90-day survival. Multivariate analysis with stepwise selection identified a higher serum RANTES level at AE to be a significant predictor of 90-day survival, including after adjustment for HRCT pattern. Multivariate analysis with stepwise selection suggested that a marked increase in the serum IL-10 level on day 8 could predict 90-day mortality. Conclusions: A higher serum RANTES level at AE the time of diagnosis predicted a good survival outcome, and an elevated serum IL-10 level on day 8 predicted a poor survival outcome. Trial registration number: UMIN000014969.